2003
DOI: 10.2136/vzj2003.5800
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Heat Flux Measurement by Flux Plates of Contrasting Design and Thermal Conductivity

Abstract: The thermal conductivity (λ) of soils may vary by a factor of about 4 for a range of field soil water contents. Measurement of soil heat flux (G) using a heat flux plate with a fixed λ distorts heat flow through the plates and in the adjacent soil. The objectives of this research were to quantify heat flow distortion errors for soil heat flux plates of widely contrasting designs and to evaluate the accuracy of a previously reported correction. Six types of commercially available heat flux plates with varying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…Another source of error in heat flux plate measurements is liquid water and vapor flow disruption since plates can block liquid water and vapor flow [Sauer et al, 2003;Ochsner et al, 2006]. If a heat flux plate is installed near the soil surface (e.g., at 2 cm depth), the plate might overestimate the soil heat flux by more than 20%, as demonstrated by Ochsner et al [2006] and Peng et al [2015].…”
Section: 1002/2017jd027160mentioning
confidence: 99%
See 1 more Smart Citation
“…Another source of error in heat flux plate measurements is liquid water and vapor flow disruption since plates can block liquid water and vapor flow [Sauer et al, 2003;Ochsner et al, 2006]. If a heat flux plate is installed near the soil surface (e.g., at 2 cm depth), the plate might overestimate the soil heat flux by more than 20%, as demonstrated by Ochsner et al [2006] and Peng et al [2015].…”
Section: 1002/2017jd027160mentioning
confidence: 99%
“…The reliability of this approach is highly dependent on accurate measurements from the SHF plate and accurate estimation of S G . The plate method is simple to implement, but a number of studies have demonstrated that the performance of the plate method is likely to suffer from several errors, including heat flow distortion and liquid water and vapor flow disruption [Sauer et al, 2003;Ochsner et al, 2006]. Fortunately, the use of self-calibrating SHF plates (HFP01SC, Huskeflux Thermal Sensors) can substantially reduce errors caused by heat flow distortion and improve the accuracy of G z measurements [Ochsner et al, 2006[Ochsner et al, , 2007Peng et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the simplicity and durability, evidence suggests that the soil heat flux plate is prone to errors during the estimation of G z in field, especially errors from heat flow distortion which may be induced by the differences of thermal conductivity between the plate and the surrounding soil (Sauer et al 2003;Peng et al 2015). Due to the varied near-surface soil moisture, the thermal conductivity of the soil surrounding the plate was varying (Lu et al 2007) and not always matched with that of the plate (Philip 1961).…”
Section: Plate Calorimetric Methodsmentioning
confidence: 99%
“…Ochsner et al [15] concluded that the heat flux plate underestimates soil heat flux because of the low plate thermal conductivity, thermal contact resistance, and latent heat transfer effects. However, this is the main method to obtain the experimental soil heat flux and widely used in studies of surface energy balance closure [27][28][29].…”
Section: Introductionmentioning
confidence: 99%